STUDI TENTANG BENTUK MOTIF, TEKNIK PENGERJAAN DAN KOMBINASI WARNA BORDIR PADA USAHA BORDIR HJ. ROSMA KECAMATAN IV ANGKEKKABUPATEN AGAM - Dra. Ernis, M.Pd., Nikmatul Husna, Drs. Erwin A, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2016)
Problems were found in the Embroidery Business Hj. Rosma wasHj. Rosma as teachers form motifs, processing techniques and color combinations on this effort has died, along with many students Hj. Rosma who has resigned. This led the authors perceived its own concerns with the preservation of shape motifs, processing techniques and color combinations on Embroidery Business Hj. Rosma.Method this study was to describe the shape of the motive,construction techniques, and the combination of colors of embroidery on embroidery Enterprises Hj. Rosma. The research method used descriptive qualitative method. The type of data in the form of primary and secondary data. The technique of collecting data through observation, interviews, documentation and literature. Data analysis is done by qualitative descriptive analysis, in which the author describes the data and researchresults in narrative form that is both creative and deep and showed the characteristics of a natural.The results of that study, the form contained in the embroidery motif embroidery business Hj. Rosma was Naturalist motifs form the plant and animal motifs such as leaves motif chain, Bungo Gadang, Tampuak Bungo, Kaluak Paku, Melati, Mawar, Anggrek, Kuda Laut, Ikan Mas and Kupukupu. Geometric motifs such as the motif rectangles, and circles. Embroidery techniques used there are two techniques: embroidery techniques suji cair and Kerancang (include: Kerancang Pusat, Kerancang Rel, Kerancang Kacau and Kerancang Kacang) color combinations of colorcombinations Analogus, Monocromatic and Complementer. Expected results of this embroidery craft products can be preserved and enhanced ability to compete and market share by providing training and knowledge about the understanding and way of making sketches of motifs, techniquesand color combinations.